RETRACTED: Fossil Energy Demand and Economic Development in BRICS Countries - Wang, Hong; Asif Amjad, Muhammad; Arshed, Noman; Mohamed, Abdullah; Ali, Shamsher; Haider Jafri, Muhammad Afaq; Khan, Yousaf Ali (Frontiers in Energy Research, 2022)
Energy is considered as the oxygen of an economy because all economic activities are done through energy consumption. The present study empirically analyzes the relationship of coal, oil and gas consumption with economic development in BRICS countries using annual panel data from 1990 to 2019. Fully Modified Ordinary Least Squares is used to empirically estimate the quadratic function of coal, oil and gas consumption, while the control variables are exports of goods and services and labor force participation. This model shows that coal and natural gas consumption follows the inverted U-shaped relationship with HDI, while oil consumption shows a negative relationship with HDI. In the policy recommendation, the BRICS countries should decrease the share of coal, oil and gas consumption because it is inversely affecting economic development. These countries should move towards alternative clean energy resources by using advanced technology such as the gasification process. The environmental agencies should play a significant role in decreasing coal and oil consumption, especially in the two countries of BRICS, China and India.